PENGARUH BIAYA BAHAN BAKU DAN PENGENDALIAN BIAYA PRODUKSI TERHADAP HASIL PRODUKSI STUDI KASUS PADA EMPAT SERANGKAI MANDIRI PRODUK SURPET SAYIDA - Muarif, Samsul (Ekonis: Jurnal Ekonomi dan Bisnis, 2025)
Abstract: This study uses case study methodology and causality method, and is quantitative. The research sample for 36 months on the financial statements of raw material costs, production cost control, and production results. The data used are primary data. The results of the study indicate that raw material costs vary each month as a result of changes in the price of foam and rasfur fabric, the main raw materials used to make surpet. With a positive value, production cost control has been running well and costs can still be controlled. The company determines the standard raw material cost, labor cost standard, factory overhead cost standard, and variations of each component of production costs in order to increase production cost efficiency. Controlling production costs and raw material costs at the same time has a major impact on output. In part, production results are significantly improved by raw material costs, and production results are significantly improved by production cost control. Keywords: Raw Material Costs, Production Cost Control, Production Results